Investigating the Attitude on Blended Learning Adaptability among Nursing Faculty Students - Kurnia Budiyanti; Syahrul Ramadhan; Mukhaiyyar Mukhaiyyar (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
Recent decades have witnessed substantial transformations in education, particularly with the advent of information and communication technology. Among the notable innovations is blended learning (BL), increasingly adopted as a mainstream approach for foreign language education in higher institutions, particularly for Recognition of Prior Learning (RPL) classes catering to working students. This paper addresses the growing prominence of blended learning in nursing programs, combining traditional face-to-face instruction with online components. Despite its rise, there remains a gap in understanding how nursing faculty and students perceive and adapt to BL compared to traditional methods. This study investigates students' attitudes towards BL in Nursing Faculty, comparing RPL and regular class students. Employing quantitative research with a survey design, the study likely included closed-ended and Likert scale questions to gauge respondents' attitudes. Results from 148 participants reveal a positive response towards BL adaptability, with 80.4% expressing favorable views. Both RPL and regular class students showed similar positive categorizations, with minor differences in average scores. These findings suggest a high level of adaptability to blended learning among students, underscoring its potential for higher education. Insights gleaned from this study are poised to inform the advancement of blended instruction in academia